The role of socialization in personality development (Journal of Philosophy Culture and Political Science, 2018)
On the basis of the analysis of various scientific concepts and theories the article defines social, philosophical essence and conceptual bases of socialization and development of human personality. The study of modern theoretical and methodological approaches to the phenomenon of socialization and development of the individual allows to show its social, philosophical, spiritual, moral, mental aspects, as well as the importance in all areas of social and humanitarian research. And also, characterizing the personality as a social entity the features of socialization of the personality are considered. In complexity of social life actualizarea problem include human social integrity, social structure of society. The basic concept that describes this kind of inclusion is «socialization», which allows a person to become a member of society. Under socialization refers to the process of entering the individual into society, which creates changes in the social structure of society and in the structure of the individual. Therefore, the role of socialization and human personality development is analyzed.Key words: personality, socialization, society, culture, self-determination.